Bangabandhu and Bangladesh: analysing contemporary society and politics - Karim, A.H.M Zehadul (Shrabon Prokashoni, 2016)
After a rule of two hundred years, the British proclaimed independence of the Indian sub-continent by dividing it into two major countries, namely India and Pakistan in the year 1947. Pakistan comprised of two different regions, namely West Pakistan and East Pakistan (present-day Bangladesh), which remained geographically disjointed from each other with a distance of two thousand miles across the Indian Territory. Since its inception, the union of Bangladesh with Pakistan has been very unhappy and volatile from the socio-economic, political and lingua-cultural perspectives where the people of Bangladesh are often treated as colonial segmentation of Pakistan. After being freed from the British rule, Bangladesh has now fallen into another kind of colonial rule of Pakistan where they exploit the people of Bangladesh in terms of their political rights and economic shares.